The Role of Company Size, Litigation Risk on Accounting Conservatism with Financial Distress as a Moderating Variable - Anniswati Rosyida, Isnaini (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to examine the effect of Company Size, Litigation Risk on Accounting Conservatism using a moderating variable, namely Financial Distress in Manufacturing Companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This study uses a quantitative descriptive approach. The sampling technique in this study uses purposive sampling. The data collection technique in this study uses a secondary data method, namely the annual report of manufacturing companies in the food and beverage sub-sector. And for the data processing technique, SEM-PLS 4 is used. With a P-Value <0.05, the Moderation variable has an effect on X1 and Y. Finally, in this study it can be concluded that Financial Distress has an effect on Litigation Risk and Accounting Conservatism because the P-Value is 0.029 <0.05 so that this variable is predicted to be accepted.